Tender Auctions with Existing Operators Bidding - Vincent A.C. van den Berg (Tinbergen Institute, 2013)
Consider a government tendering a facility, such as an airport or utility, where one bidder owns a competing facility. With a standard auction, this existing operator bids above the auctioned facility's expected profit, as winning means being a monopolist instead of a duopolist. This auction leads to an unregulated outcome which hurts welfare. A consumer-price auction can alleviate this problem. With complementing facilities, the existing operator offers a price below marginal cost and is more likely to win than other bidders; with substitutes, it is less likely to win. Often, the advantaged bidder always wins, eliminating competition for the field.
Keywords: D43; D44; L13; L51; 330; Tender auction; existing operators; Advantaged bidder; Price auction; Auktionstheorie